Answer:
see explanation
Step-by-step explanation:
73.
18 = 3x
(divide both sides by 3 )
6 = x
( multiply both sides by
)
6
= 3x [
×
= 3 ]
divide both sides by 3
x = 2![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
74.
24 = 2x
( divide both sides by 2 )
12 = x
( multiply both sides by
)
12
= 2x ( divide both sides by 2 )
x = 6![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
75.
9
× x = 18
( divide both sides by 9
)
x = 2
76.
2 = x ×
( multiply both sides by
)
2
= 4x ( divide both sides by 4 )
x = ![\frac{\sqrt{3} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B3%7D%20%7D%7B2%7D)
Answer:
2.33
Step-by-step explanation:
If you put the numbers into the radius formula you should end up with this number hope this helps:)
Answer:
I think the answer is B.7070-(-7460)
I'm sorry if it was wrong..
Answer:
? = (x + 7)
Step-by-step explanation:
2x^2 + 15x + 7 = (2x + 1) (?)
1. First you need to figure out what multiplied by 2x will give you 2x^2, which is x.
2. Then you need to find what would give you 15x. In this case because you have the 1 in (2x + 1), you already know that there is going to be an extra x. So, what times 2x gives you 14x? It's 7.
3. Lastly you need to make sure that 1 multiplied with 7 is equal to 7 and combine like terms.
4. Check: (2x + 1) (x + 7) =
2x^2 + 14x + 1x + 7 =
2x^2 + 15x + 7
A) 2/6 = 1/3
1/3 = 1/3
True
------
b) 1/3 > 2/4
1/3 > 1/2
False
------
c) 1/8 > 3/4
False
------
d) 2/5 < 1/2
True
------
e) 4/12 < 1/6
False
------
f) 3/5 = 7/10
False
------
This is all just a process of simplifying fractions down.
The only 'true' statements there are is option A and D.